Dampak Sosial Ekonomi Pemberdayaan Masyarakat Kelompok Tani Swadaya Oleh Industri PT. Manakkara Unggul Lestari - A. Octamaya Tenri Awaru; Nurulmiati Nurulmiati; Nita Talia; Mustika Mustika; Melfin Dwi Sofiana; Yulianti Yulianti (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
Process and efforts to strengthen or enable the weak. This study aims to find out how the process of community empowerment by the PT industry. Manakarra Unggul Lestari and the impact of this empowerment. The research method used was phenomenological qualitative. The data obtained were analyzed using interpretive phenomenological analysis (IPA). The results of the study explained: (1) The empowerment process begins with socialization carried out by the PT, this socialization contains methods for planting and developing what is called an oil palm plant. Those who are already members of independent farmer groups are given the opportunity to order oil palm seeds at a low cost. So that many people who previously did not have a job, now work as oil palm farmers. (2) The positive impact of this independent farmer group is the ability of the community to get more optimal results and income than usual. While the negative impact is the emergence of environmental pollution caused by four-wheeled vehicles used as transporters of oil palm crops, the presence of air pollution such as the amount of dust that appears during the dry season can cause people to experience a decrease in body immunity.